1967
DOI: 10.1002/jsfa.2740180208
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of disulfoton by soil

Abstract: Adsorption of the systemic insecticide disulfoton (diethyl S-[a-(ethylthio) ethyl] phosphorothiolothionate) by soil was studied using a wet slurry technique. Extraction of soils and solutions after equilibration showed that more disulfoton was lost from solution than could be extracted from soil, principally because of microbial alteration and adsorption by glass. In two contrasting soils equilibration was complete by 3 h and air-dry soils in the laboratory adsorbed similarly to the moist field soils from whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1969
1969
2005
2005

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…The adsorption of disulfoton on various soils was correlated with organic matter content and pH (Graham-Bryce 1967). Moisture also affected disulfoton adsorption; if desorption experiments were performed while the soil was still wet, adsorption appeared completely reversible.…”
Section: +mentioning
confidence: 99%
“…The adsorption of disulfoton on various soils was correlated with organic matter content and pH (Graham-Bryce 1967). Moisture also affected disulfoton adsorption; if desorption experiments were performed while the soil was still wet, adsorption appeared completely reversible.…”
Section: +mentioning
confidence: 99%
“…As with most soil-applied pesticides (2,4,6,8,15,23), adequate soil moisture is required for satisfactory ethofumesate activity. Hartley (11), using wall barley (Hordeum murinum L.) as an indicator species, found that the activity of ethofumesate decreased as the soil moisture at the time of application decreased from 50 to 10% (w/w).…”
Section: Introductionmentioning
confidence: 99%
“…centration with time is degradation. Substantial degradation of other compounds can occur in the relatively short times (<4 days) in which adsorption-desorption experiments are conducted (6,13,15). Although negligible amounts of 14 C0 2 and DCPU were found for either soil up to the 72-h equilibration, substantial amounts of DCPMU were found in the Palouse soil-solution extract ( Figure 3); up to 19% of methazole initially added had degraded to DCPMU within 72 h. No emphasis should be placed on the effect of initial concentration on the rate of degradation.…”
Section: Resultsmentioning
confidence: 99%